Stress fracture after implant removal from the tibia reconstructed by the induced membrane technique: A case report. (June 2022) - Lim, Eic Ju; Kent, William T.; Sakong, Seungyeob; Son, Whee Sung; Cho, Jae-Woo; Oh, Jong-Keon
Abstract: Background: The induced membrane technique promotes vascularization and corticalization of the grafted bone and has become one of the mainstays in treatment of segmental bone defects. However, there are clinical concerns regarding the quality of bony consolidation using the induced membrane technique including a thin cortex formation and cortical notching after consolidation. We present the case of a tibial stress fracture in the bone reconstructed by the induced membrane technique after implant removal. Case: A 49-year-old male presented post-traumatic osteomyelitis of the right tibia and was treated with staged segmental bone resection leading to an 11 cm defect which was reconstructed using the induced membrane technique. The patient requested implant removal at 33 months after bony consolidation. Four months after implant removal, he developed acute, atraumatic leg pain due to a tibial stress fracture caused by small notching in the reconstructed tibial segment. His stress fracture treated with intramedullary nailing and later healed uneventfully. Conclusion: Caution is warranted prior to implant removal from bone reconstructed by the induced membrane technique as cortical notching may result in stress fractures.